Students’ Needs on English Reading Comprehension Materials in Indonesian Higher Education - Syaripuddin, Rahmatullah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the needs of students related to English reading materials at the university level. The total number of students who became the research sample at Muhammadiyah Parepare University was 46 students. This study used a quantitative method by means of which students filled out a questionnaire with three assessment indicators namely frequency, interest and level of proficiency in reading comprehension of English. The findings of this study indicate that reading articles from magazines and newspapers, e-mail, and online articles, reading English manuals or booklets, reading reports, textbooks, and book references, understanding and interpreting the meaning of graphs, tables, and figures, understanding specific information, understanding general information, and identifying main ideas are materials needed by students in teaching English in reading comprehension skills